Harnessing Empathy: The Power of Emotional Resonance in Live Streaming Sales and the Moderating Magic of Product Type - Shizhen Bai; Fang Jiang; Qiutong Li; Dingyao Yu; Yongbo Tan (Journal of Theoretical and Applied Electronic Commerce Research)
The emotional expressions in live streaming e-commerce possess a strong contagious effect, enabling viewers to easily resonate with the specific emotions conveyed by the streamers and consciously build an empathy transmission chain. This study constructs a regression model based on the emotional contagion theory and explores the impact of empathy between streamers and viewers on sales performance. Using data from 30 live streams, totaling 22,707 min, from one of China’s most popular live streaming rooms, “East Buy”, between February and April 2024, we demonstrate the significant positive impact of empathy between streamers and viewers on sales. Additionally, product type positively moderates this relationship. The unexpected thing is that live streaming time does not significantly affect the relationship between empathy and sales. This study employs text sentiment analysis methods to extract emotional features from the streamers’ speech and real-time comments from viewers. Our research extends the application of emotional contagion theory to the context of live-streaming e-commerce, enriches the literature on emotional interaction in service marketing, and provides practical insights for live-streaming platforms and streamers. Streamers can optimize marketing strategies and achieve sales goals by creating a more engaging and empathetic live-streaming experience.